Silence is a scary sound : and other stories on living through the terrible twos and threes - Edwards, Clint, 1982- (Page Street Publishing Co., 2019)
"I'd gone to college. I'd written for the New York Times. I had a solid credit score. How did I end up here? After his breakout hit book I'm Sorry ... Love, Your Husband, Clint Edwards has more laugh-out-loud tales, this time from the "terrible twos" and "threenager" phases each of his kids went through. His relatable toddler stories leave parents and caregivers cackling, and remind us all that no one is the perfect parent. In fact, sometimes the only thing that gets Clint through the day is thinking about when his kids grow up ... and all the ways he can finally exact his revenge. Like leaving a leaky sippy cup full of milk to rot under the back seat of his daughter's car, or waking up at 4 a.m. to incessantly ask his son for a cheese stick. With essays like Locking Doors Is Hilarious Until the Fire Department Arrives, Poop Doesn't Go Easily Down a Tub Drain, Dad's Never the Favorite, and Face It--You'll Never Pee Alone, Clint knows exactly what's "terrible" about the twos ... and threes."--Provided by publisher.